2021
DOI: 10.1038/s41467-021-26926-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism for the loss of mRNA activity in lipid nanoparticle delivery systems

Abstract: Lipid nanoparticle (LNP)-formulated mRNA vaccines were rapidly developed and deployed in response to the SARS-CoV-2 pandemic. Due to the labile nature of mRNA, identifying impurities that could affect product stability and efficacy is crucial to the long-term use of nucleic-acid based medicines. Herein, reversed-phase ion pair high performance liquid chromatography (RP-IP HPLC) was used to identify a class of impurity formed through lipid:mRNA reactions; such reactions are typically undetectable by traditional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 30 publications
0
105
0
Order By: Relevance
“…Later, scientists developed ionizable LNPs to ameliorate this side effect. However, a recent study showed that these ionizable lipids may include impurities, leading to a loss of mRNA activity, while these impurities are difficult to identify with the traditional techniques [ 186 ]. In addition, due to some shortcomings of the LNPs, such as easy oxidation and degradation, nonuniform preparation protocols, and high recurrence rate, large-scale industrial production has been difficult to achieve [ 187 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, scientists developed ionizable LNPs to ameliorate this side effect. However, a recent study showed that these ionizable lipids may include impurities, leading to a loss of mRNA activity, while these impurities are difficult to identify with the traditional techniques [ 186 ]. In addition, due to some shortcomings of the LNPs, such as easy oxidation and degradation, nonuniform preparation protocols, and high recurrence rate, large-scale industrial production has been difficult to achieve [ 187 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, authors showed that stability was protected upon freeze-thaw cycles when cryoprotectants such as sucrose or trehalose [93]-two excipients used in the marketed vaccines-were used. In this regard, more recently, a novel class of mRNA reactivity that leads to loss of activity has been reported: the formation of mRNA-LNP adducts though the covalent union between some reactive lipids and the nucleobase [24,94]. It is also worth noting that mRNA could potentially have more stability issues than siRNA, as it is a longer and more complex molecule.…”
Section: Stability Considerationsmentioning
confidence: 99%
“…They constitute an integral part of the mandatory quality control as well as the isolation of high purity intermediates required for products whose synthesis is performed serially. It must be highlighted that in mRNA production, utmost purity of the final product is not only a safety issue, but also a matter of therapeutical efficacy and shelf-life longevity, since contaminants can compromise both shelf-life of the finalized product as well as illicit unwanted immune responses [ 85 , 86 , 87 ]…”
Section: Analytical Approachesmentioning
confidence: 99%
“…Advances in biotechnology require the development of state-of-the-art analytical techniques to ensure that LNP-encapsulated mRNAs are QC-labeled and tested to ensure their safety and efficacy. Modern techniques including liquid (LC), or gas chromatography (GC) and mass spectrometry (MS) are therefore being applied to analyze lipid and mRNA attributes or to detect and quantify lipid impurities [ 86 ].…”
Section: Analytical Approachesmentioning
confidence: 99%
See 1 more Smart Citation